2003
DOI: 10.1016/s0960-9822(03)00291-4
|View full text |Cite
|
Sign up to set email alerts
|

Flamingo Regulates R8 Axon-Axon and Axon-Target Interactions in the Drosophila Visual System

Abstract: Photoreceptors (R cells) in the Drosophila retina connect to targets in three distinct layers of the optic lobe of the brain: R1-R6 connect to the lamina, and R7 and R8 connect to distinct layers in the medulla. In each of these layers, R axon termini are arranged in evenly spaced topographic arrays. In a genetic screen for mutants with abnormal R cell connectivity, we recovered mutations in flamingo (fmi). fmi encodes a seven-transmembrane cadherin, previously shown to function in planar cell polarity and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 23 publications
3
107
0
Order By: Relevance
“…Further analysis revealed that two mutant lines were allelic to previously identified fmi mutations Gao et al, 2000;Lee et al, 2003). Flamingo has been shown to be present and well studied in peripheral sensory cells, axons of central nervous system of embryos and larvae (Sweeney et al, 2002), in axons and growth cones of photoreceptors in 3 rd instar larvae and mid-pupae Senti et al, 2003). However, its presence and roles in the motor system remains unknown.…”
Section: Flamingo Is Expressed In Axons and At Synapsesmentioning
confidence: 84%
See 3 more Smart Citations
“…Further analysis revealed that two mutant lines were allelic to previously identified fmi mutations Gao et al, 2000;Lee et al, 2003). Flamingo has been shown to be present and well studied in peripheral sensory cells, axons of central nervous system of embryos and larvae (Sweeney et al, 2002), in axons and growth cones of photoreceptors in 3 rd instar larvae and mid-pupae Senti et al, 2003). However, its presence and roles in the motor system remains unknown.…”
Section: Flamingo Is Expressed In Axons and At Synapsesmentioning
confidence: 84%
“…This observation may be consistent with an earlier Northern blot analysis showing that RNA levels drop dramatically from embryos to larvae (Chae et al, 1999). However, this may not suggest that Flamingo is all absent, as it is still transiently expressed in larval photoreceptors Senti et al, 2003). To further examine Flamingo expression in the CNS (brain lobes plus the VNC) in embryos and developing larvae, we used Western blot to detect protein levels.…”
Section: Fmi Mutants Grow Slowly During 3 Rd Instar Stages and Are Slmentioning
confidence: 99%
See 2 more Smart Citations
“…In each ommatidium, the axons of R1-R8 photoreceptor cells terminate in different layers of the optic lobe: R1-R6 synapse in the lamina, R7 terminates in the M6 layer of the medulla, and R8 in the more superficial M3 layer. Flamingo is required for the layer-specific targeting of axons, a process mediated by a pathway distinct from that used in establishing ommatidial polarity [26,27] .…”
Section: Flamingo and Neuronal Morphogenesismentioning
confidence: 99%